2015
DOI: 10.5152/npa.2015.7160
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil-Induced Psychosis: A Case Report

Abstract: Modafinil is used in the treatment of excessive day time sleepiness associated with several clinical conditions. It can also be used for affective stimulation for working late and/or concentrating for a long time. The reported cases of psychosis associated with modafinil use in the literature, have medical or psychiatric diorders. There is only one reported case without medical or psychiatric disorder but developed modafinil related psychosis, which is a case under simulated shift work in laboratory conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…More studies are needed to highlight their specific effect on behavioral pathways and how their preferential activation of specific brain areas may influence the behavioral response. Similarly, it has to be carefully considered that such drugs may expose patients to a small risk of psychosis and mania [70, 8082].…”
Section: Resultsmentioning
confidence: 99%
“…More studies are needed to highlight their specific effect on behavioral pathways and how their preferential activation of specific brain areas may influence the behavioral response. Similarly, it has to be carefully considered that such drugs may expose patients to a small risk of psychosis and mania [70, 8082].…”
Section: Resultsmentioning
confidence: 99%
“…We found two case reports in the literature worth mentioning. One is the case of a patient taking only 100 mg of modafinil who developed psychosis, without psychiatric history 26. The second is a patient with history of psychosis whose symptoms recurred when modafinil 200 mg was added to quetiapine 600 mg 27.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study, modafinil-induced psychosis was identified in only a few case reports (58,59).…”
Section: Pharmacotherapy and Psychotic Disorder In Narcoleptic Patientsmentioning
confidence: 95%